Migrant rights at work : law's precariousness at the intersection of immigration and labour - Berg, Laurie (Milton Park, Abingdon, Oxon : Routledge, 2016)
'Public debates about immigration and membership have intensified alongside developed economies' increasing reliance on temporary migrant workers. While most agree that temporary migrant workers are entitled to the general protection of employment laws, temporary immigration programs necessitate the restriction of rights to residence, occupational and geographic mobility, and full social protections. This book examines the ways in which immigration law and enforcement reconfigure the relationships between migrant workers and employers, causing uncertainty and worsening working conditions. Taking the regulatory reforms of Australia as a key case-study, Laurie Berg explores how the influence of immigration law extends beyond its functions in regulating admission to and exclusion from a country. Berg asks where should differences lie between temporary and permanent residents, what further restrictions should apply to migrants who lack immigration authorisation, and where should the line be drawn between exploitation and legitimate employment. In presenting an analytical approach to issues of temporary labour migration, the book develops a unique theoretical framework, contending that the concept of precariousness, rather than equality or vulnerability, is the most fruitful way to evaluate and address issues of temporary migrant labour. The book will be of great interest to scholars and practitioners of immigration law and employment law and policy'--
Migrant Rights at Work -- Inclusion and Precariousness -- Keeping up the'Australian Standard' : The Regulation of Temporary Migrant Workers in Australia -- Worker Protection for which Workers? : Successive Reforms to the Temporary Skilled 457 Visa Program -- How Immigration Controls Produce Unauthorised Migrant Workers -- A Jurisprudence of Unauthorised Work -- Employer Sanctions against Unauthorised Workers -- Working with Coercion : Labour Trafficking in Australia -- Getting our Priorities Straight : Connections Between Forced Labour and Labour -- Conclusion.
Includes bibliographical references (pages 297-315) and index.
Keywords: Foreign workers -- Legal status, laws, etc. -- Australia